Chronic kidney disease in patients with psoriasis, chronic opisthorchiasis and at their combination - T. A. Kolosovskaya; S. A. Khardikova; Ye. V. Kalyuzhina; L. G. Surkova; K. A. Zamyshevskaya; K. A. Varlacheva (Бюллетень сибирской медицины)
The aim of the investigation was to study of features of сhronic kidney disease in patients with chronic opisthorchiasis (CO), psoriasis (Ps) and their combination. Examination was performed on 360 patients with CO, 100 patients with Ps, 50 patients with Ps combinated CO and 30 healthy subjects. In addition to complete clinical and instrumental examination accepted in specialised clinic, biopsy of kidney was conducted. The interrelation of intensity of sclerous processes in kidneys and renoprival syndrome with duration of CO and activity of Ps was found. Dehelmintization with biltricid promoted improvement of functional state of kidneys.